Well-ordered nanoparticle arrays for floating gate memory applications - Kuruoglu, Furkan; Calskan, Murat; Serin, Merih; Erol, Ayse (IOP Publishing Ltd, 2020)
A non-volatile floating gate memory device containing well-ordered Au nanoparticles (NPs) is fabricated as a metal-oxide-semiconductor capacitor structure. With superior control on the size, shape and position of nanoparticles, the presented nano-floating gate memory (NFGM) device possesses almost perfect precision of device geometry. The well-ordered Au NPs embedded within the memory device exhibit large memory window at low operation voltages (8.8V @ 15V), fast operation time (<10(-4) s) and good retention (up to 10(7) s). In this work, the structural properties of the NFGM device are correlated with the examined electrical properties. The current results are compared with the other studies in the literature to emphasis the advantages of the precise ordering and geometry of the NPs.
Keywords: non-volatile memory; Au nanoparticle; well-ordered; Coulomb blockade; electron beam lithography; RAPID-THERMAL-OXIDATION; DIELECTRICS; THICKNESS; DEVICE; LAYER; Science & Technology - Other Topics; Materials Science; Physics